Cognitive influences on risk-seeking by rhesus macaques, - Benjamin Y. Hayden; Sarah R. Heilbronner; Amrita C. Nair; Michael L. Platt (Judgment and Decision Making, 2008)
Humans and other animals are idiosyncratically sensitive to risk, either preferring or avoiding options having the same value but differing in uncertainty. Many explanations for risk sensitivity rely on the non-linear shape of a hypothesized utility curve. Because such models do not place any importance on uncertainty extitper se, utility curve-based accounts predict indifference between risky and riskless options that offer the same distribution of rewards. Here we show that monkeys strongly prefer uncertain gambles to alternating rewards with the same payoffs, demonstrating that uncertainty itself contributes to the appeal of risky options. Based on prior observations, we hypothesized that the appeal of the risky option is enhanced by the salience of the potential jackpot. To test this, we subtly manipulated payoffs in a second gambling task. We found that monkeys are more sensitive to small changes in the size of the large reward than to equivalent changes in the size of the small reward, indicating that they attend preferentially to the jackpots. Together, these results challenge utility curve-based accounts of risk sensitivity, and suggest that psychological factors, such as outcome salience and uncertainty itself, contribute to risky decision-making.